Fears that faculty members face from conducting online exams and the resulting procedures in Libyan universities (Journal of Pure & Applied Sciences, 2020)
This paper dealt with the concerns facing faculty members from conducting exams via the Internet in Libyan higher education institutions and the procedures resulting therefrom in universities, and it started from the fact that there is a problem represented by the failure of higher education institutions in Libya to provide the requirements of e-learning programs, which reflects negatively on the educational system When the world witnessed a revolution in computer technology and distance education, e-learning and virtual universities have recently emerged as alternatives to traditional education, especially in light of the crises that the world is witnessing from wars or the spread of epidemics. This research paper aims to know the concerns facing faculty members in Libyan universities from evaluation and the possibility of using the exam via the Internet as an alternative to the traditional exam. The study consisted of (86) a faculty member in the Libyan universities who were randomly chosen, and the researchers applied a questionnaire consisting of (18) items whose validity and reliability were tested, the results of the study indicated that there are negative perceptions of the faculty members in the Libyan universities about exams via the Internet. The study recommended conducting introductory lectures and workshops for faculty members and students to introduce remote exams and the possibility of using and using them during the school year, as well as providing the necessary infrastructure for electronic communications.